Implementation of Religious and Moral Values Through the Habit of Maintaining Personal and Environmental Cleanliness at RA Hasan Munadi Banggle Gunung Gangsir Beji Pasuruan - Nanang Rokhman Saleh; Muhammad Syaikhon (al-Afkar, Journal For Islamic Studies, 2024)
The impact of globalization and the rapidly development of the times marked by digitalization has made moral education in early childhood decrease drastically. Many children still commit deviant acts, acts of violence, behave badly and commit acts that are prohibited in religion. This can happen because of the lack of religious and moral cultivation from an early age. Therefore, the most important thing to do is an effort to form a moral human being with morals in the form of implementing religious and moral values through the habit of maintaining personal and environmental cleanliness. Raudhatul Athfal (RA) Hasan Munadi is one of the educational institutions under the auspices of the Ministry of Religion which pays attention to the application of religious and moral values through the habit of maintaining personal and environmental cleanliness. This research aims to analyze the application of religious and moral values through the habit of maintaining personal and environmental cleanliness at RA Hasan Munadi Gunung Gangsir Beji Pasuruan. The data sources in this study consist of primary sources in the form of school data, while secondary data are the results of observation, interviews, and documentation. Data collection techniques through observation, interview, and documentation methods. The data analysis technique uses the Miles and Huberman analysis method so that it can be seen the application of religious and moral values through the habit of maintaining personal and environmental cleanliness at RA Hasan Munadi. The results of the research show that the application of religious and moral values through the habit of maintaining personal and environmental cleanliness at RA Hasan Munadi is carried out well in accordance with the expectations and achievements of development.